Plant-based Diet in Athletes: A Game Changer or Just a Trend? - Słowikowska, Aleksandra; Sztyler-Krąkowska, Marcelina; Wąsowicz, Agnieszka; Smyl, Natalia; Teofilak, Mateusz; Szatkowska, Julia; Śpiołek, Olga; Siwiec, Jan; Kędziora, Franciszek; Fabian, Dariusz (Journal of Education, Health and Sport, 2024)
Introduction: Nowadays, a plant-based diet is gaining increasing popularity. Guidance on adopting this diet can be found in scientific literature, as well as through social media and advertisements promoting a wide range of new products appearing on store shelves. By reviewing scientific sources, we decided to analyze the principles of a plant-based diet, its associated benefits, as well as the potential negative aspects of its implementation, particularly among athletes. Aim of the study: This review aims to analyse the literature concerning the impact of a plant- based diet on accomplishments, endurance, and health, especially for athletes. Materials and methods: The authors conducted an extensive review of available articles on PubMed, ScienceDirect, Cochrane, UpToDate, Google Scholar, and Pubmed databases, using keywords such as vegan, vegetarian, plant-based, civilization diseases, healthy lifestyle, athletes, strength, accomplishments, endurance. Studies accessed between 2016-2024 were included in this review. Results and conclusions: A plant-based diet is a valuable option for athletes, offering benefits such as improved recovery, reduced oxidative stress, and alignment with sustainable practices. When properly planned to address potential nutrient deficiencies, it can effectively support athletic performance, including strength and endurance, without compromising health. Thus, for athletes seeking ethical, health-conscious, or environmentally sustainable dietary patterns, a plant-based diet is indeed worth considering.